Peripartum effects of synthetic oxytocin: the good, the bad, and the unknown - Rashidi, Mahmoud; Maier, Eduard; Dekel, Sharon; Sütterlin, Marc; Wolf, Robert Christian; Ditzen, Beate; Grinevich, Valéry; Herpertz, Sabine (Neuroscience & biobehavioral reviews, 2022)
The first clinical applications of oxytocin (OT) were in obstetrics as a hormone to start and speed up labor and to control postpartum hemorrhage. Discoveries in the 1960s and 1970s revealed that the effects of OT are not limited to its peripheral actions around birth and milk ejection. Indeed, OT also acts as a neuromodulator in the brain affecting fear memory, social attachment, and other forms of social behaviors. The peripheral and central effects of OT have been separately subject to extensive scrutiny. However, the effects of peripheral OT - particularly in the form of administration of synthetic OT (synOT) around birth - on the central nervous system are surprisingly understudied. Here, we provide a narrative review of the current evidence, suggest putative mechanisms of synOT action, and provide new directions and hypotheses for future studies to bridge the gaps between neuroscience, obstetrics, and psychiatry.